Automatic method for individual parcellation of manganese-enhanced magnetic resonance imaging of rat brain - Bao, Zhiguo; Zhang, Tianhao; Pan, Tingting; Zhang, Wei; Zhao, Shilun; Liu, Hua; Nie, Binbin (Frontiers in Neuroscience, 2022)
Aims: To construct an automatic method for individual parcellation of manganese-enhanced magnetic resonance imaging (MEMRI) of rat brain with high accuracy, which could preserve the inherent voxel intensity and ROI morphological characteristics simultaneously. Methods and Results: The transformation relationship from standardized space to individual space was obtained by firstly normalizing individual image to the Paxinos space and then inversely transformed. On the other hand, all the regions defined in the atlas image were separated and resaved as binary mask images. Then, transforming the mask images into individual space via the inverse transformations and reslicing using 4th B-spline interpolation algorithm. The boundary of these transformed regions were further refined by image erosion and expansion operator, and finally combined together to generate the individual parcellations. Moreover, two groups of MEMRI images were used for evaluation. We found that the individual parcellations were satisfied, and the inherent image intensity was preserved. The statistical significance of case-control comparisons was further optimized. Conclusions: We have constructed a new automatic method for individual parcellation of rat brain MEMRI images, which could preserve the inherent voxel intensity and further be beneficial in case-control statistical analyses. This method could also be extended to other imaging modalities, even other experiments species. It would facilitate the accuracy and significance of ROI-based imaging analyses.